AL Amyloidosis Complicated by Persistent Oral Bleeding. (7th May 2015) - Marconcini, Luiz Antonio Liarte; Stewart, Forrest Marc; Sonntag, Lisa; Stevens, Emily; Burwick, Nicholas
Abstract : A case of amyloid light chain (AL) amyloidosis is presented here with uncontrolled bleeding after a nonsurgical dental procedure, most likely multifactorial in nature, and consequently treated with a multidisciplinary approach.